(untitled) (Research, Society and Development, 2022)
The weevil Sitophilus zeamais (Coleoptera: Curculionidae) is one of the main pests of stored corn. The use of synthetic insecticides is the main strategy for its management, which can cause unwanted effects such as the selection of resistant insects and residues. In this case, the search for less impactful products is desirable. This work evaluated the lethal and sublethal action of bioinsecticides formulated from Beauveria bassiana (Boveril®), Metarhizium anisopliae (Metarril®) and Isaria fumosorosea (Octane®) over S. zeamais. The lethal effect evaluations revealed that after 240 hours of exposure by direct contact at a concentration of 1.0 × 107 conidia.mL-1, Boveril® caused a mortality of 77%, being higher than that verified for Metarril® (10.8 %) and Octane® (9.4%). Residual contact with 1.0 × 107 conidia.mL-1 caused a maximum mortality of 5% for the evaluated bioinsecticides. The evaluation of sublethal effects didn’t indicate significant differences in the instantaneous growth rates (ri) of S. zeamais populations held for 90 days in substrate sprayed with 1.0 × 107 conidia.mL-1 of each of the bioinsecticides and a control where sterilized distilled water was used. In the conventional choice attractiveness test, the Boveril® treatment presented 11.2% of insects, indicating possible repellency, with no differences between the other bioinsecticides and the control formed by sterilized distilled water. Boveril® was the most promising among the tested bioinsecticides, showing a probable repellency and causing a significant mortality of S. zeamais via direct contact.